PENDAFTARAN HAK ATAS TANAH ADAT DI KOTA DENPASAR - A A NGR Raka Dani Wiryantha; I Made Suwitra; I Made Sepud (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2017)
ABSTRACT Legal protection in the registration of indigenous land rights in Denpasar still so unclear in the public and little or not cause problems such as: 1) How does the legal protection in the registration of customary land by BAL, 2) How Implications Conflict in the registration of customary land in Denpasar. This type of research is research of normative law, the approach to legislation, Concepts, Analytical, Case, and Comparative Law, Materials used in the form of primary legal materials, secondary, tertiary, and then analyzed by Technical Interpretation. The study found that the legal protection in the registration of customary land according to the BAL described in Article 3 and Article 4 of the registration of the land on which rang to provide protection and legal certainty, as the enactment of Government Regulation No. 24 of 1997, the order of article 19 of Law land laws. The implications of conflict in the registration of customary land in the city of Denpasar because of their customary land rights of control in an individual or individuals who aims into the land conflicts, which make land registration becomes blocked, land conflicts resolved by the General Court and the Administrative Court. While the land conflict resolution outside the court to do is negotiation, consensus and mediation. Negotiations carried out by way of which the conflicting parties to sit together to find the best way of resolving conflicts with the principle that the settlement was no injured party (win-win), the two sides no one feels aggrieved. Keywords: Legal Protection, Right to Land, the Land Registry, Implications Conflict.